Perceptual grouping can affect the online control of goal-directed hand movements - Emily M. Crowe; Danai T. Vorgia; Liz R. van Hout; Jeroen B. J. Smeets; Eli Brenner (Experimental Brain Research, 2026)
If the target of a goal-directed arm movement is suddenly displaced, the movement is quickly adjusted accordingly. There are situations in which grouping gives the impression that many items have been displaced, although the change that determines the direction of the perceived displacement occurs far from the target. When a single item disappears from one end of a row of items just when an item appears at the other end, it looks as if a single item is displaced from one end to the other (element motion). But if the whole row of items briefly disappears when this change occurs, the whole row seems to have been displaced (group motion). We asked participants to move their finger to a purple target item at the centre of a row of equally spaced black items. Hand movements towards the target were adjusted in the direction of both element and group motion. The adjustment of the movement was especially clear for short rows of items. Importantly, the response was much more vigorous under conditions that give rise to group motion than under conditions that give rise to element motion. Thus, a displacement that is propagated to the target through grouping can affect goal-directed movements.

Hindsight informs foresight: revisiting millennial forecasts of impacts and status of rocky shores in 2025 - Stephen J. Hawkins; Kathryn A. O'Shaughnessy; George M. Branch; Laura Airoldi; Simon Bray; Paul Brooks; Michael T. Burrows; Juan Carlos Castilla; Tasman P. Crowe; Thomas W. Davies; Louise B. Firth; Keith Hiscock; et al. (Marine Pollution Bulletin, 2025)

Environmental exposure assessment in the international prospective study of Chronic Kidney Disease of UnceRtain Etiology (CKDu) in Agricultural Communities (CURE) research consortium: Design and protocol development - Marvin González-Quiroz; Anna Aceituno; Shuchi Anand; Alexander van Geen; Lawrence S. Engel; Emmanuel Jarquin; Clemens Ruepert; Nicole Villegas-González; Mariela Arias-Hidalgo; Nora Franceschini; Daylin Anchía-Pastrán; Karla Solano-Diaz; et al. (Science of The Total Environment, 2025)

Unveiling growth and carbon composition of macroalgae with different strategies under global change - Camino F. de la Hoz; Paul R. Brooks; Jennifer Coughlan; Inés Mazarrasa; Elvira Ramos; Samuel Sainz-Villegas; Araceli Puente; Jose A. Juanes; Tasman P. Crowe (Marine Environmental Research, 2025)

Investigating leatherback surface behavior using a novel tag design and machine learning - Rick Rogers; Kate H. Choate; Leah M. Crowe; Joshua M. Hatch; Michael C. James; Eric Matzen; Samir H. Patel; Christopher R. Sasso; Liese A. Siemann; Heather L. Haas (Journal of Experimental Marine Biology and Ecology, 2024)

Habitat structure shapes temperate reef assemblages across regional environmental gradients - Tim Jackson-Bué; Ally J. Evans; Peter J. Lawrence; Paul R. Brooks; Sophie L. Ward; Stuart R. Jenkins; Pippa J. Moore; Tasman P. Crowe; Simon P. Neill; Andrew J. Davies (Science of The Total Environment, 2024)

The influence of environmental context on community composition in artificial rockpools associated with seawalls - Veronica Farrugia Drakard; Ally J. Evans; Tasman P. Crowe; Pippa J. Moore; Jennifer Coughlan; Paul R. Brooks (Marine Environmental Research, 2024)

A response-surface approach into the interactive effects of multiple stressors reveals new insights into complex responses - Paul R. Brooks; Mark Anthony Browne; Lisandro Benedetti-Cecchi; Devin A. Lyons; Tasman P. Crowe (Frontiers in Marine Science, 2023)
Understanding the difficult to predict interactive effects of anthropogenic stressors is recognized as one of the major challenges facing environmental scientists and ecosystem managers. Despite burgeoning research, predicting stressor interactions is still difficult, in part because the same two stressors can interact, or not, depending on their intensities. While laboratory experiments have provided useful insights about how organisms respond to serial doses of single stressors, we lack ‘response-surface’ field experiments in which naturally occurring assemblages are exposed to multiple types and concentrations of stressors. Here we used a field-based dosing system combined with a ‘response-surface’ design to test the individual and combined effects of two stressors (copper and chlorpyrifos) at five concentrations of each, for a total of 25 replicated treatments (n=4). After six weeks of dosing, chemical uptake and impacts at several levels of biological organization in mussel assemblages were measured. Stressor combinations produced interactive effects that would not have been revealed without using this replicated ‘response-surface approach’. Results show that non-additive effects of multiple stressors may be more complex and more common than previously thought. Additionally, our findings suggest that interactive effects of multiple stressors vary across levels of organization which has implications for monitoring and managing the chemical, biological and ecological impacts of priority pollutants in the real world.

Population structure and reproductive states of the dogwhelk Nucella lapillus differ between artificial structures and natural rocky shores - Bryan Thompson; Paul R. Brooks; Veronica Farrugia Drakard; Fiona Kubin; Hannah S. Earp; Ignacio Alvarez-Cienfuegos; Pippa J. Moore; Tasman P. Crowe (Marine Environmental Research, 2023)

Using valve gape analysis to compare sensitivity of native Mytilus edulis to invasive Magallana gigas when exposed to heavy metal contamination - David B. Kelleghan; Luke O'Callaghan; Freddie Huggard; Tasman P. Crowe; Paul R. Brooks (Marine Environmental Research, 2023)

Artificial rockpools: Seaweed colonisation and productivity vary between sites but are consistent across environmental contexts - Veronica Farrugia Drakard; Ally J. Evans; Tasman P. Crowe; Pippa J. Moore; Jennifer Coughlan; Paul R. Brooks (Marine Environmental Research, 2023)

Colonisation after disturbance on artificial structures: The influence of timing and grazing - Veronica Farrugia Drakard; Paul R. Brooks; Tasman P. Crowe (Marine Environmental Research, 2023)

Targeting de novo loss-of-function variants in constrained disease genes improves diagnostic rates in the 100,000 Genomes Project - Eleanor G. Seaby; N. Simon Thomas; Amy Webb; Helen Brittain; Ana Lisa Taylor Tavares; J. C. Ambrose; P Arumugam; R Bevers; M Bleda; F Boardman-Pretty; C. R. Boustred; H Brittain; et al. (Human Genetics, 2023)
Background Genome sequencing was first offered clinically in the UK through the 100,000 Genomes Project (100KGP). Analysis was restricted to predefined gene panels associated with the patient’s phenotype. However, panels rely on clearly characterised phenotypes and risk missing diagnoses outside of the panel(s) applied. We propose a complementary method to rapidly identify pathogenic variants, including those missed by 100KGP methods. Methods The Loss-of-function Observed/Expected Upper-bound Fraction (LOEUF) score quantifies gene constraint, with low scores correlated with haploinsufficiency. We applied DeNovoLOEUF, a filtering strategy to sequencing data from 13,949 rare disease trios in the 100KGP, by filtering for rare, de novo, loss-of-function variants in disease genes with a LOEUF score < 0.2. We compared our findings with the corresponding patient’s diagnostic reports. Results 324/332 (98%) of the variants identified using DeNovoLOEUF were diagnostic or partially diagnostic (whereby the variant was responsible for some of the phenotype). We identified 39 diagnoses that were “missed” by 100KGP standard analyses, which are now being returned to patients. Conclusion We have demonstrated a highly specific and rapid method with a 98% positive predictive value that has good concordance with standard analysis, low false-positive rate, and can identify additional diagnoses. Globally, as more patients are being offered genome sequencing, we anticipate that DeNovoLOEUF will rapidly identify new diagnoses and facilitate iterative analyses when new disease genes are discovered.

The population structure, sex ratio and reproductive potential of limpets (Patella spp.) on natural shores and artificial structures in the Irish Sea - Hannah S. Earp; Ruby George; Paul R. Brooks; Veronica Farrugia Drakard; Bryan J. Thompson; Benjamin Fisher; Róisín Hayden; Tasman P. Crowe; Pippa J. Moore (Marine Environmental Research, 2023)

Assessing discards in an illegal small-scale fishery using fisher-led reporting - T. Mendo; J. Mendo; J. M. Ransijn; I. Gomez; P. Gil-Kodaka; J. Fernández; R. Delgado; A. Travezaño; R. Arroyo; K. Loza; P. McCann; S. Crowe; et al. (Reviews in Fish Biology and Fisheries, 2022)
About a third of all marine fish in the world are caught in Small-Scale Fisheries (SSF). SSF are increasingly recognised as essential for food security and livelihoods for vulnerable and economically fragile communities globally. Although individual SSF vessels are usually perceived as having little impact on the ecosystem, the cumulative impact of gear type and number of vessels may be substantial. Bottom trawling is a common fishing method that can greatly influence the marine ecosystem by damaging the seafloor and generating high levels of discards. However, appropriate sampling coverage using on-board observer programmes to collect these data from SSF are rare, as they are expensive and pose logistical constraints. A mobile App was used to assess whether self-reporting by fishers could provide reliable fine-scale information on fishing effort and discards over time in an illegal shrimp trawling fishery in northern Peru. Maps depicting the spatial distribution of trawling effort and the proportion of discards from observers and fishers were compared using the Similarity in Means (SIM) Index, which ranges from 0 when spatial patterns differ completely to 1 when spatial patterns are very similar. High levels of agreement between spatio-temporal patterns of effort (SIM Index = 0.81) and discards (0.96) were found between fisher and observer maps. Moreover, far greater spatial coverage was accomplished by fishers, suggesting that self-reporting via an App represents a useful approach to collect reliable fisheries data as an initial step for effective monitoring and management of these fisheries.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

The use of environmental DNA metabarcoding and quantitative PCR for molecular detection of marine invasive non-native species associated with artificial structures - Laura M. Gargan; Paul R. Brooks; Siobhan R. Vye; Joseph E. Ironside; Stuart R. Jenkins; Tasman P. Crowe; Jens Carlsson (Biological Invasions, 2022)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Patterns of mortality in endangered Cook Inlet beluga whales: Insights from pairing a long‐term photo‐identification study with stranding records - Tamara L. McGuire; Kim E. W. Shelden; Gina K. Himes Boor; Amber D. Stephens; John R. McClung; Christopher Garner; Caroline E. C. Goertz; Kathleen A. Burek‐Huntington; Greg O'Corry‐Crowe; Bruce Wright (Marine Mammal Science, 2021)
Mortality is a demographic metric crucial for understanding the dynamics of endangered populations such as Cook Inlet beluga whales (CIBWs, Delphinapterus leucas ), but patterns of mortality are currently not well understood for CIBWs, making decisions about recovery actions challenging. We combined long‐term photo‐ID data from approximately 420 individual belugas identified during the period 2005–2017 with stranding data from 95 dead belugas to identify patterns of mortality with respect to age, sex, geographic range, cause of death, and to estimate minimum mortality rates. Reported mortality was greatest for adults of reproductive age, followed by calves, with fewer subadults and no adults older than 49 years in the stranding data set despite lifespans of 70+ years reported in other beluga populations. Dead females and males were evenly represented. Live stranding was the predominant assigned cause of death but represented only ~33% of deaths of known cause. Causal factors for the majority of deaths and live strandings are unknown. Annual mortality estimated from reported carcasses relative to total population size averaged 2.2%. Our analysis advances our current understanding of mortality patterns in CIBWs but linking a greater proportion of carcasses to photo‐ID individuals would further improve our understanding; we conclude with recommendations for achieving this.

A global analysis of complexity–biodiversity relationships on marine artificial structures - Elisabeth M. A. Strain; Peter D. Steinberg; Maria Vozzo; Emma L. Johnston; Marco Abbiati; Moises A. Aguilera; Laura Airoldi; J. David Aguirre; Gail Ashton; Maritina Bernardi; Paul Brooks; Benny K. K. Chan; et al. (Global Ecology and Biogeography, 2021)
Aim Topographic complexity is widely accepted as a key driver of biodiversity, but at the patch‐scale, complexity–biodiversity relationships may vary spatially and temporally according to the environmental stressors complexity mitigates, and the species richness and identity of potential colonists. Using a manipulative experiment, we assessed spatial variation in patch‐scale effects of complexity on intertidal biodiversity. Location 27 sites within 14 estuaries/bays distributed globally. Time period 2015–2017. Major taxa studied Functional groups of algae, sessile and mobile invertebrates. Methods Concrete tiles of differing complexity (flat; 2.5‐cm or 5‐cm complex) were affixed at low–high intertidal elevation on coastal defence structures, and the richness and abundance of the colonizing taxa were quantified after 12 months. Results The patch‐scale effects of complexity varied spatially and among functional groups. Complexity had neutral to positive effects on total, invertebrate and algal taxa richness, and invertebrate abundances. However, effects on the abundance of algae ranged from positive to negative, depending on location and functional group. The tidal elevation at which tiles were placed accounted for some variation. The total and invertebrate richness were greater at low or mid than at high intertidal elevations. Latitude was also an important source of spatial variation, with the effects of complexity on total richness and mobile mollusc abundance greatest at lower latitudes, whilst the cover of sessile invertebrates and sessile molluscs responded most strongly to complexity at higher latitudes. Conclusions After 12 months, patch‐scale relationships between biodiversity and habitat complexity were not universally positive. Instead, the relationship varied among functional groups and according to local abiotic and biotic conditions. This result challenges the assumption that effects of complexity on biodiversity are universally positive. The variable effect of complexity has ramifications for community and applied ecology, including eco‐engineering and restoration that seek to bolster biodiversity through the addition of complexity.

Examining the roles of working memory and visual attention in multiple object tracking expertise - David J. Harris; Mark R. Wilson; Emily M. Crowe; Samuel J. Vine (Cognitive Processing, 2020)
When tracking multiple moving targets among visually similar distractors, human observers are capable of distributing attention over several spatial locations. It is unclear, however, whether capacity limitations or perceptual–cognitive abilities are responsible for the development of expertise in multiple object tracking. Across two experiments, we examined the role of working memory and visual attention in tracking expertise. In Experiment 1, individuals who regularly engaged in object tracking sports (soccer and rugby) displayed improved tracking performance, relative to non-tracking sports (swimming, rowing, running) ( p = 0.02, η p 2 = 0.163), but no differences in gaze strategy ( ps > 0.31). In Experiment 2, participants trained on an adaptive object tracking task showed improved tracking performance ( p = 0.005, d = 0.817), but no changes in gaze strategy ( ps > 0.07). They did, however, show significant improvement in a working memory transfer task ( p < 0.001, d = 0.970). These findings indicate that the development of tracking expertise is more closely linked to processing capacity limits than perceptual–cognitive strategies.

Extracellular nucleic acid scavenging rescues rats from sulfur mustard analog-induced lung injury and mortality - Nithya Mariappan; Maroof Husain; Iram Zafar; Vinodkumar Singh; Kenneth G. Smithson; David R. Crowe; Jean-Francois Pittet; Shama Ahmad; Aftab Ahmad (Archives of Toxicology, 2020)

Future Directions in the Research and Management of Marine Snakes - Vinay Udyawer; Peter Barnes; Xavier Bonnet; François Brischoux; Jenna M. Crowe-Riddell; Blanche D’Anastasi; Bryan G. Fry; Amber Gillett; Claire Goiran; Michael L. Guinea; Harold Heatwole; Michelle R. Heupel; et al. (Frontiers in Marine Science, 2018)

Characterization of large basking shark Cetorhinus maximus aggregations in the western North Atlantic Ocean - L. M. Crowe; O. O'Brien; T. H. Curtis; S. M. Leiter; R. D. Kenney; P. Duley; S. D. Kraus (Journal of Fish Biology, 2018)
Cetorhinus maximus aggregations recorded during extensive aerial survey efforts off the north‐eastern United States between 1980 and 2013 included aggregations centring on sightings with group sizes of at least 30 individuals. These aggregations occurred in summer and autumn months and included aggregation sizes of up to 1398 individuals, the largest aggregation ever reported for this species. The aggregations were associated with sea surface temperatures of 13–24° C and chlorophyll‐a concentrations of 0·4–2·6 mg m −3 and during one aggregation, a high abundance of zooplankton prey was present. Photogrammetric tools allowed for the estimation of total body lengths ranging between 4 and 8 m. Characterization of these events provides new insight into the potential biological function of large aggregations in this species.

Velocity measurements in inclined negatively buoyant jets - A. T. Crowe; M. J. Davidson; R. I. Nokes (Environmental Fluid Mechanics, 2016)

Heterotrophic bacteria from an extremely phosphate‐poor lake have conditionally reduced phosphorus demand and utilize diverse sources of phosphorus - Mengyin Yao; Felix J. Elling; CarriAyne Jones; Sulung Nomosatryo; Christopher P. Long; Sean A. Crowe; Maciek R. Antoniewicz; Kai‐Uwe Hinrichs; Julia A. Maresca (Environmental Microbiology, 2016)
Summary Heterotrophic P roteobacteria and A ctinobacteria were isolated from L ake M atano, I ndonesia, a stratified, ferruginous (iron‐rich), ultra‐oligotrophic lake with phosphate concentrations below 50 nM. Here, we describe the growth of eight strains of heterotrophic bacteria on a variety of soluble and insoluble sources of phosphorus. When transferred to medium without added phosphorus ( P ), the isolates grow slowly, their RNA content falls to as low as 1% of cellular dry weight, and 86–100% of the membrane lipids are replaced with amino‐ or glycolipids. Similar changes in lipid composition have been observed in marine photoautotrophs and soil heterotrophs, and similar flexibility in phosphorus sources has been demonstrated in marine and soil‐dwelling heterotrophs. Our results demonstrate that heterotrophs isolated from this unusual environment alter their macromolecular composition, which allows the organisms to grow efficiently even in their extremely phosphorus‐limited environment.

HIV eradication symposium: will the brain be left behind? - B. J. Brew; K. Robertson; E. J. Wright; M. Churchill; S. M. Crowe; L. A. Cysique; S. Deeks; J. V. Garcia; B. Gelman; L. R. Gray; T. Johnson; J. Joseph; et al. (Journal of NeuroVirology, 2015)

Functional analyses of three acyl‐ CoA synthetases involved in bile acid degradation in P seudomonas putida DOC 21 - Álvaro Barrientos; Estefanía Merino; Israël Casabon; Joaquín Rodríguez; Adam M. Crowe; Johannes Holert; Bodo Philipp; Lindsay D. Eltis; Elías R. Olivera; José M. Luengo (Environmental Microbiology, 2015)
Summary P seudomonas putida DOC 21, a soil‐dwelling proteobacterium, catabolizes a variety of steroids and bile acids. Transposon mutagenesis and bioinformatics analyses identified four clusters of steroid degradation ( std ) genes encoding a single catabolic pathway. The latter includes three predicted acyl‐ CoA synthetases encoded by stdA1 , stdA2 and stdA3 respectively. The Δ stdA1 and Δ stdA2 deletion mutants were unable to assimilate cholate or other bile acids but grew well on testosterone or 4‐androstene‐3,17‐dione ( AD ). In contrast, a Δ stdA3 mutant grew poorly in media containing either testosterone or AD . When cells were grown with succinate in the presence of cholate, Δ stdA1 accumulated Δ 1/4 ‐3‐ketocholate and Δ 1,4 ‐3‐ketocholate, whereas Δ stdA2 only accumulated 7α,12α‐dihydroxy‐3‐oxopregna‐1,4‐diene‐20‐carboxylate ( DHOPDC ). When incubated with testosterone or bile acids, Δ stdA3 accumulated 3aα‐ H ‐4α(3′propanoate)‐7aβ‐methylhexahydro‐1,5‐indanedione ( HIP ) or the corresponding hydroxylated derivative. Biochemical analyses revealed that StdA1 converted cholate, 3‐ketocholate, Δ 1/4 ‐3‐ketocholate, and Δ 1,4 ‐3‐ketocholate to their CoA thioesters, while StdA 2 transformed DHOPDC to DHOPDC ‐ CoA . In contrast, purified StdA 3 catalysed the CoA thioesterification of HIP and its hydroxylated derivatives. Overall, StdA 1, StdA 2 and StdA 3 are acyl‐ CoA synthetases required for the complete degradation of bile acids: StdA 1 and StdA 2 are involved in degrading the C ‐17 acyl chain, whereas StdA 3 initiates degradation of the last two steroid rings. The study highlights differences in steroid catabolism between P roteobacteria and A ctinobacteria .

Spine pruning in 5xFAD mice starts on basal dendrites of layer 5 pyramidal neurons - Sarah E. Crowe; Graham C. R. Ellis-Davies (Brain Structure and Function, 2014)

Disturbance of intertidal soft sediment assemblages caused by swinging boat moorings - R. J. H. Herbert; T. P. Crowe; S. Bray; M. Sheader (Hydrobiologia, 2009)

Green manure effects on soil quality in relation to suppression of Verticillium wilt of potatoes - N. Ochiai; M. L. Powelson; F. J. Crowe; R. P. Dick (Biology and Fertility of Soils, 2008)

Histamine induces interleukin-6 expression in the human synovial sarcoma cell line (SW982) through the H1 receptor - S. L. Wang; S. Malany; Q. Wang; M. A. Santos; P. D. Crowe; R. A. Maki (Inflammation Research, 2006)

Diet of Pacific sleeper shark, a potential Steller sea lion predator, in the north‐east Pacific Ocean - M. F. Sigler; L. B. Hulbert; C. R. Lunsford; N. H. Thompson; K. Burek; G. O’Corry‐Crowe; A. C. Hirons (Journal of Fish Biology, 2006)
Pacific sleeper sharks Somniosus pacificus were captured near Steller sea lion Eumetopias jubatus rookeries during the period when Steller sea lion pups are most vulnerable to Pacific sleeper shark predation (first water entrance and weaning). Analysis of stomach contents revealed that teleosts were the dominant prey in August and cephalopods were the dominant prey in May ( n = 198). Marine mammals were found in 15% of stomachs regardless of season, but no Steller sea lion tissues were detected. Molecular genetic analysis identified grey whale Eschrichtius robustus and harbour seal Phoca vitulina remains in some Pacific sleeper shark stomachs. Most mammals were cetacean and at least 70% of the cetaceans were probably scavenged. Although Pacific sleeper shark and Steller sea lion ranges overlapped, so predation could potentially occur, the diet study suggested that predation on Steller sea lions is unlikely, at least when pups first enter the water or during weaning. Harbour seals were infrequent prey and may have been consumed alive. Pacific sleeper sharks consume fast‐swimming prey like Pacific salmon Oncorhynchus sp., most likely live animals rather than scavenged animals. Pacific sleeper sharks appeared to be opportunistic consumers of the available prey and carrion, feeding both on the bottom and in the water column, and their diet shifted to teleosts and cetacean carrion as the fish grew larger.

New records of planktonic cyanobacteria in New Zealand freshwaters - S.A. Wood; A. L. M. Crowe; J. G. Ruck; R. G. Wear (New Zealand Journal of Botany, 2005)
New records of planktonic cyanobacteria in New Zealand freshwaters are reported. Identified for the first time were one genus, Sphaerocavum , represented by one species, and one species of Apha‐nocapsa , five species of Microcystis , and three of Anabaena. Microcystis panniformis has previously been recorded only from tropical or subtropical regions. Descriptions, drawings, and photographs of species are presented.

Structure–Activity of Valencenoid Derivatives and Their Repellence to the Formosan Subterranean Termite - Betty C. R. Zhu; Gregg Henderson; Anne M. Sauer; Ying Yu; William Crowe; Roger A. Laine (Journal of Chemical Ecology, 2003)

Dose and Enantiospecific Responses of White Pine Cone Beetles, Conophthorus coniperda, to α-Pinene in an Eastern White Pine Seed Orchard - Daniel R. Miller; Christopher M. Crowe; Christopher Asaro; Gary L. Debarr (Journal of Chemical Ecology, 2003)

The information content of Doppler ultrasound signals from the fetal heart - S. A. Shakespeare; J. A. Crowe; B. R. Hayes-Gill; K. Bhogal; D. K. James (Medical & Biological Engineering & Computing, 2001)

Application of empirical mode decomposition to heart rate variability analysis - J. C. Echeverría; J. A. Crowe; M. S. Woolfson; B. R. Hayes-Gill (Medical & Biological Engineering & Computing, 2001)

Compact long-term recorder for the transabdominal foetal and maternal electrocardiogram - J. F. Piéri; J. A. Crowe; B. R. Hayes-Gill; C. J. Spencer; K. Bhogal; D. K. James (Medical & Biological Engineering & Computing, 2001)

Middle Pleistocene interglacial deposits at Barling, Essex, England: evidence for a longer chronology for the Thames terrace sequence - D. R. Bridgland; R. C. Preece; H. M. Roe; R. M. Tipping; G. R. Coope; M. H. Field; J. E. Robinson; D. C. Schreve; K. Crowe (Journal of Quaternary Science, 2001)
Results are presented from a multidisciplinary study of fossiliferous interglacial deposits on the northern side of the Thames estuary. These fill a channel cut into London Clay bedrock and overlain by the Barling Gravel, a Thames–Medway deposit equivalent to the Lynch Hill and Corbets Tey Gravels of the Middle and Lower Thames, respectively. The channel sediments yielded diverse molluscan and ostracod assemblages, both implying fully interglacial conditions and a slight brackish influence. Pollen analysis has shown that the deposits accumulated during the early part of an interglacial. Plant macrofossils, particularly the abundance of Trapa natans , reinforce the interglacial character of the palaeontological evidence. A beetle fauna, which includes four taxa unknown in Britain at present, has allowed quantification of palaeotemperature using the mutual climatic range method ( T max 17 to 26 °C; T min −11 to 13 °C). A few vertebrate remains have been recovered from the interglacial deposits, but a much larger fauna, as well as Palaeolithic artefacts, is known from the overlying Barling Gravel. The age of the interglacial deposits is inferential. The geological context suggests a late Middle Pleistocene interglacial, part of the post‐diversion Thames system and therefore clearly post‐Anglian. This conclusion is supported by amino acid ratios from the shells of freshwater molluscs. The correlation of the overlying Barling Gravel with the Lynch Hill/Corbets Tey aggradation of the Thames valley constrains the age of the Barling interglacial to marine oxygen isotope stages 11 or 9. The presence of Corbicula fluminalis and Pisidium clessini confirms a pre‐Ipswichian (marine oxygen isotope substage 5e) age and their occurrence in the early part of the interglacial cycle at Barling precludes correlation with marine oxygen isotope stage 11, as these taxa occur only later in that interglacial at sites such as Swanscombe and Clacton. Thus by process of elimination a marine oxygen isotope stage 9 age would appear probable. Copyright © 2001 John Wiley & Sons, Ltd.

Implications of grazing and burning of grasslands on the sustainable use of francolins (Francolinus spp.) and on overall bird conservation in the highlands of Mpumalanga province, South Africa - R. Jansen; R.M. Little; T.M. Crowe (Biodiversity and Conservation, 1999)

Bacteraemia in the Adult Intensive Care Unit of a Teaching Hospital in Nottingham, UK, 1985-1996 - M. Crowe; P. Ispahani; H. Humphreys; T. Kelley; R. Winter (European Journal of Clinical Microbiology & Infectious Diseases, 1998)

Bacteraemia in the adult intensive care unit of a teaching hospital in Nottingham, UK, 1985–1996 - M. Crowe; P. Ispahani; H. Humphreys; T. Kelley; R. Winter (European Journal of Clinical Microbiology & Infectious Diseases, 1998)

Phylogeography, population structure and dispersal patterns of the beluga whale Delphinapterus leucas in the western Nearctic revealed by mitochondrial DNA - G. M. O'Corry‐Crowe; R. S. Suydam; A. Rosenberg; K. J. Frost; A. E. Dizon (Molecular Ecology, 1997)
The recent evolutionary history, population structure and movement patterns of beluga whales in the western Nearctic were inferred from an analysis of mitochondrial DNA control region sequence variation of 324 whales from 32 locations representing five summer concentration areas in Alaska and north‐west Canada. Phylogenetic relationships among haplotypes were inferred from parsimonious networks, and genetic subdivision was examined using haplotypic frequency‐based indices and an analysis of variance method modified for use with interhaplotypic distance data. MtDNA relationships were characterized by a series of star‐like phylogenies which, when viewed in conjunction with information on haplotype frequency and distribution, suggested a rapid radiation of beluga whales into the western Nearctic following the Pleistocene, and an early divergence of the Beaufort Sea from the Chukchi and Bering Seas subpopulations. Overall nucleotide diversity was low (0.51%) yet all major summering concentrations were significantly differentiated (Φ ST = 0.33) from one another. Stratification of samples by gender and age from the three northernmost subpopulations suggested that female cohorts from neighbouring subpopulations were more differentiated than males. Further stratification of adult animals by age revealed that older adults were substantially less subdivided among locations than younger adults, particularly for males, suggesting that dispersal, although limited, is biased toward older adult males. Overall, the patterns of mtDNA variation in beluga whales indicated that the summering concentrations are demographically, if not phyletically distinct. Population structure appears to be maintained primarily by natal homing behaviour, while asymmetries in dispersal may be associated with the type of mating system.

Extracellular polysaccharide of Nostoc commune (Cyanobacteria) inhibits fusion of membrane vesicles during desiccation - Donna R. Hill; Thomas W. Keenan; Richard F. Helm; Malcolm Potts; Lois M. Crowe; John H. Crowe (Journal of Applied Phycology, 1997)

Niska: A maincrop chipping potato cultivar with high specific gravity and good quality after storage - D. R. Lynch; D. Kichefski; S. Peloquin; C. S. Schaupmeyer; L. la Croix; D. Waterer; Wm. T. Andrew; J. Holley; N. Crowe; B. McConnell; G. A Nelson; B. Rex (American Journal of Potato Research, 1991)

Multichannel transmission of proprioceptive input to motoneurons - B. W. A. Feenstra; R. H. J. Tanke; A. Crowe (Biological Cybernetics, 1985)

Ribosomal RNA gene number and sequence divergence in the diploid-tetraploid species pair of north American hylid tree frogs - L. A. Toivonen; D. T. Crowe; R. J. Detrick; S. W. Klemann; J. C. Vaughn (Biochemical Genetics, 1983)

The effects of ? motor stimulation on the interpretation of signals from muscle spindles - A. Crowe; M. Naeije; R. H. J. Tanke (Biological Cybernetics, 1982)

A method for the interpretation of signals in afferent nerves from muscle spindles - A. Crowe; M. Naeije; R. H. J. Tanke (Biological Cybernetics, 1980)